Answer:
Step-by-step explanation yes
Answer:
a. y^ -1 = e^x +2
Step-by-step explanation:
y = ln (x-2)
Exchange x and y
x = ln (y-2)
Solve for y
Raise each side with a base of e
e^ x = e^(ln(y-2)
e^x = y-2
Add 2 to each side
e^x +2 =y
Answer:
Step-by-step explanation:
Just use the distributive property.
(4y^2-3)(4y+3)
= 4y^2(4y+3) - 3(4y+3)
= 16y^3 + 12y^2 - 12y - 9
Answer:
1. $155 ≥ $31.50p + $13.25
2. p ≤ 4
Its just a matter of subbing ur numbers into the formula given
1. d = rt
when r = 144 and t = 18
now we sub
d = 144 * 18
d = 2592 <==
2. d = rt
when r = 56 and t = 3.5
sub
d = 56 * 3.5
d = 196 <==
3. A = L * W
when L = 2 ft and W = 15 inches....this one u have to convert to inches...2 ft = 24 inches...so L = 24 and W = 15
A = 24 * 15
A = 360 in^2 <==
4. A = L * W
L = 3m and W = 32 cm...have to convert to cm.....1 m = 100 cm...so 3 m = 300 cm
A = 300 * 32
A = 9600 cm^2 <==
u basically do the same for all the others....its just a matter of subbing and solving